2020
DOI: 10.3390/scipharm88040048
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Drug Interaction in Severely Obese Individuals and Associated Factors: Baseline Results from a Clinical Trial

Abstract: The prevalence of obesity is increasing worldwide and is commonly associated with comorbidities. The use of several drugs is often necessary, which leads to Potential Drug Interactions (PDI) that may increase the morbidity and mortality. This study aimed to analyze the prevalence of drug interaction and its association with socio-demographics, health status, and drug use in severely obese individuals. Baseline data from a randomized clinical trial registered at Clinicaltrial.gov (NCT02463435) were used. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(62 reference statements)
1
0
0
Order By: Relevance
“…Consequently the prevalence of DDI in the current study is very low (1.0%) compared to studies of DDIs for people with diabetes conducted in India, Pakistan, Finland, France and Brazil which reported 39%-62%. 59-63 In line with the findings in this study, only 1.7% of the interactions were reported to be severe in a study conducted in Brazil. 64 Similarly, no severe interactions was reported in a study conducted in India that reported only moderate DDIs.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently the prevalence of DDI in the current study is very low (1.0%) compared to studies of DDIs for people with diabetes conducted in India, Pakistan, Finland, France and Brazil which reported 39%-62%. 59-63 In line with the findings in this study, only 1.7% of the interactions were reported to be severe in a study conducted in Brazil. 64 Similarly, no severe interactions was reported in a study conducted in India that reported only moderate DDIs.…”
Section: Discussionsupporting
confidence: 86%